Rotavirus, respiratory syncytial virus and non‐rotaviral gastroenteritis analysis of hospital readmissions in England and Wales. (9th January 2013) - Pockett, Rhys D.; Campbell, David; Carroll, Stuart; Rajoriya, Fiona; Adlard, Nick
Abstract Aim To quantify readmissions with infectious diseases and differences in readmission patterns. Methods Using the CHKS database, children <5 years admitted to hospital in England and Wales, between 2000 and 2008, with rotavirus (RV), respiratory syncytial virus (RSV) or non‐rotaviral gastroenteritis (NRV) were identified. All admissions within a 30‐day prior period were similarly identified, and the proportion of readmissions was calculated. Results There were 365, 693 admissions for RV, RSV and NRV; 17.2% were readmissions. In 36% of cases, the cause of the prior admission was also RV, RSV or NRV, with 64% having a different prior diagnosis. The majority of readmissions were within 5 days of their prior admission, the majority of those with RV (n = 2, 566/58.7%) within 3 days, NRV (n = 11 326/53.5%) within 4 days and RSV (n = 18 811/50.2%) within 9 days of prior discharge. Readmission for RV was associated with greater LOS than RSV (p < 0.001) and NRV (p < 0.001), while cost per admission was greater for RV compared to RSV (p < 0.001) and NRV (p < 0.001). Conclusions Thirty‐six percent of readmissions indicated discharge without resolution from the first admission; nosocomial infection needs to be considered as a cause in the other. Although RSV represented the largest readmission group, higher costs and longer LOS were associated with RV.